Designing a Web-Based Application Using Human- Centered Design to Enhance Postpartum Mental Health Support for Parents of Children with Special Need - Trisnadoli, Anggy; Mutya, Mita Fani Tri; Winda, Desy (ABEC Indonesia, 2024)
Postpartum mental health challenges are a significant concern for mothers, particularly for those caring forchildren with special needs. These mothers often experience heightened levels of stress, anxiety, and emotional distress,which can adversely affect their well-being and their ability to provide care. This research focuses on designing anddeveloping a web-based application to enhance mental health support specifically for this demographic, using a HumanCenteredDesign(HCD)approachtorecognizethesechallenges.Thedesignprocesscommencedwithacomprehensive user requirement analysis, utilizing qualitative methods such as interviews and quantitative surveys to gather insightsdirectly from mothers. This engagement allowed us to identify their unique needs, preferences, and pain points. Throughcollaborative discussions, we pinpointed essential features that would make the application user-friendly and effectivelysupport their mental health. The design development phase incorporated iterative feedback loops, refining the applicationbased on real user experiences and suggestions. Each iteration was guided by established HCD success indicators,ensuring alignment with users' expectations. The current goal of this research is to produce a prototype of the webapplication that addresses the mental health challenges faced by postpartum mothers. By integrating functionalities thatpromote emotional well-being and provide access to relevant resources, this application aims to empower mothers andfoster a supportive community, ultimately contributing positively to their lives and caregiving experiences.